Enhancing Pronunciation, Grammar & Fluency (PGF) Proficiency Despite Pandemic (EPP) through Flexy Supplementary Teaching and Learning Development Sheets - Xenia S. Baesa-Alfelor; Darrel M. Ocampo (Journal of English Education Forum (JEEF), 2023)
This study determined the effectiveness of the innovations, interventions and strategies through Flexy Supplementary PGF Teaching and Learning Development Sheets in times of pandemic along with pronunciation, grammar and fluency. The subjects were 30 STEM students experimentally studied using validated written-administered language proficiency test, backed up by virtual meet-ups and observation. Statistical treatment used were weighted mean and Pearson-R. Findings revealed that the students’ language proficiency before the interventions conducted did not meet the expectations with 72.67%, Beginning Proficiency Level. Along pronunciation, 36.67% were Developing Proficiency and (100%) were both beginners in both grammar, and in fluency (66.67%). After the interventions conducted, the students’ language proficiency level along pronunciation, grammar and fluency is 87.40 or approaching proficiency level Statistics showed that the r- value of 0.8658 squared to 0.75 means strong effect of the implemented interventions, innovations, and strategies in enhancing the language proficiency of students. It further implies that the flexy supplementary development kit is effective program to students in times of massive impact of Covid-19 pandemic through online and offline platforms and teachers’ flexy mode in the delivery of the language programs in STEM track.